Bridging Digital Divides: Multi-Level Governance Transformation and Poverty Reduction in Post-Pandemic Indonesia - Sarihati, Tati; Devianty, Tia (Jurnal Manajemen Pelayanan Publik, 2026)
The COVID-19 pandemic accelerated digital governance transformation worldwide, yet systematic evidence on its effectiveness for poverty reduction within developing countries' complex multi-level governance (MLG) systems remains limited. This study investigates how digital transformation in MLG coordination affects poverty reduction effectiveness in post-pandemic Indonesia (2020–2024). Employing a Systematic Review with Thematic and Bibliographic Analysis (SR-TBA) — integrating a PRISMA-compliant systematic review, inductive thematic synthesis, supplementary keyword co-occurrence visualisation, and expert validation from eight governance practitioners — we screened 294 Scopus records and retained 32 studies meeting rigorous inclusion criteria. Five thematic clusters were identified: Digital Governance Infrastructure, Social Protection Systems Digitalisation, Multi-Level Coordination Mechanisms, Community Empowerment, and Pandemic Response Acceleration. Based on the reviewed studies, 81.3% reported positive associations between digital interventions and poverty-reduction indicators. However, nearly half the corpus raised financial sustainability concerns, and expert triangulation revealed systematic divergence between academic and practitioner framings of coordination outcomes. Three theoretical contributions are advanced: a Conditional Effectiveness Framework specifying jointly necessary preconditions for durable gains; a Structured Optimism Bias thesis explaining field-level evidence distortion; and a Sustainability Trap mechanism localised to the Indonesian post-pandemic context. Findings carry direct implications for lifecycle-oriented programme design, geographic differentiation in digital investment, and social protection targeting policy.